Impacto do peso pré-gestacional e dos polimorfismos materno-neonatal dos genes fto (rs9939609) e mc4r (rs17782313) no perfil inflamatório da mãe, da placenta e nas características antropométricas e bioquímicas do neonato - Simone Fátima Gomes de Oliveira (2021)
Objectives: Obesity is a risk factor for maternal-fetal complications. Children born to obese mothers are at greater risk of developing obesity, in addition to other metabolic diseases, since metabolic changes, inflammatory and genotypic profiles link maternal nutritional status to placental function and, consequently, to the development of the neonate. The FTO (rs9939609) and MC4R (rs17782313) SNPs are consistently associated with obesity and physiological changes that lead to this disease. However, few studies have examined the maternal metabolic and inflammatory profile in association with this polymorphism in both maternal and neonatal gestational outcomes. Thus, the objective of this study was to evaluate the biochemical, inflammatory and genetic characteristics of overweight and pre-gestational obese pregnant women and their influence on maternal and neonatal anthropometric and metabolic parameters. Methodology: This is a cross-sectional study, with a sample of 165 mother-child pairs, stratified into three groups according to pre-gestational BMI (Eutrophic, Overweight and Obesity). At the time of delivery, samples of maternal peripheral blood and immediately after delivery, umbilical cord blood, placental tissue fragments, umbilical cord tissue, adipose tissue and buccal swab were collected. Anthropometric information on the neonate and the pregnant woman was taken from the medical records and the pregnant women's card, respectively. Adipokines were analyzed by ELISA method, FTO (rs9939609) and MC4R (rs17782313) genotyping was evaluated by real-time PCR. To detect significant differences, the ANOVA or Kruskal Wallis test was used for parametric and non-parametric data, respectively. For categorical variables, the chi-square test was used and for correlations, the Sperman or Pearson test was used. The multiple logistic regression model was used to determine the effect of the variables analyzed and the presence of polymorphisms. The significance level adopted for the tests was p≤0.05. Results: Maternal obesity was characterized by insulin resistance, due to higher hyperglycemia and HOMA-IR in these mothers. And yet, when compared with eutrophic mothers, those with obesity had high circulating concentrations of IL-6, TNF and resistin and in adipose tissue, we observed higher concentrations of leptin, TNF, IL-6 and IL-10. We also identified higher concentrations of leptin TNF and IL-10 in the placental compartments, both on the maternal and fetal sides. And only on the maternal face high concentrations of IL-6 lower than adiponectin. Still in the placental environment, we saw that the placenta of obese mothers had greater retention of IL-6 and TNF when compared to eutrophic mothers. We also saw that the children of obese mothers did not differ in anthropometric measurements but had higher capillary glycemia than those of eutrophic mothers and that the umbilical cord blood of these neonates had higher concentrations of leptin, TNF, IL-10 and lower concentrations of adiponectin. The presence of the risk allele for FTO (rs9939609) was shown to be more frequent in obese mothers and those with the risk allele had higher pre-gestational weight and pre-gestational BMI. Furthermore, we saw that the risk allele contributed to higher concentrations of resistin, IL-6 and TNF in maternal peripheral serum. However, we did not see interference of this polymorphism, both maternal and neonatal, in neonatal characteristics. On the other hand, the maternal MC4R SNP (rs17782313) showed no effect on maternal characteristics but was shown to reduce the birth weight of children born to mothers who had the risk allele. While the neonatal SNP also showed no effect on the characteristics of the neonate itself. Conclusion: Maternal obesity is characterized by insulin resistance associated with a genetic, systemic and local pro-inflammatory profile, which affects the placental environment, contributing to neonatal biochemical changes such as hyperglycemia.